Determinasi Profitabilitas, Leverage, Ukuran Perusahaan, Intensitas Modal dan Umur Perusahaan terhadap Tax Avoidance - Erika Rahmawati; Siti Nurlaela; Yuli Chomsatu Samrotun (Universitas Batanghari Jambi, 2021)
Tax avoidance is not a simple idea, but a general idea is a lack of resources and expertise. This study aims to examine and analyze profitability, leverage, firm size, capital intensity, and company age against tax avoidance. This type of research is quantitative research. The sampling method used was purposive sampling method with a sampling based on certain criteria. So that there are 13 companies that meet the sample criteria. The population in this study is the Manufacturing Companies in the Consumer Goods Industry Sector, the food and beverage sub-sector which are listed on the Indonesia Stock Exchange (BEI) in 2014-2019. The data used in this study are secondary data in the form of financial statements. The analysis method used is multiple regression analysis. The results of this study indicate that the variables of profitability and firm size have an effect on tax avoidance. Meanwhile, leverage, capital intensity and company age have no effect on tax avoidance.